Linking perceived social support to self-esteem and social integration among adolescents with visual impairment: A cross-lagged study - Yuan, Wei; Xie, Zhengli; Dong, Ping; Yang, Yuqin (Frontiers in Psychology, 2023)
This study examines the relationship between perceived social support and self-esteem and between perceived social support and social integration among adolescents with visual impairments. Adolescents with visual impairments (Ntime1 = 311, Ntime2 = 170) from four special education schools in eastern China participated in this study within a one-year interval. The Child and Adolescent Social Support Scale, Rosenberg Self-esteem Questionnaire, and Interpersonal Adaptation Scale were used to collect data. The results from cross-lagged panel modelling showed reciprocal positive relationships between parental support and self-esteem. Self-esteem at T1 positively predicted three other sources of perceived social support at T2: teacher support, classmate support, and close-friend support. Social integration at T1 positively predicted close-friend support at T2. This study extends understanding of the relationships among perceived social support, self-esteem, and social integration, and provides practical implications for parents, schools, and communities to improve psychosocial outcomes in adolescents with visual impairment.